Interaksi Nabi Muḥammad dengan Yahudi dan Kristen - Rifqi Muhammad Fatkhi (Refleksi, 2012)
This paper shows a number of historical information about the Prophet Muḥammad’s relationship with Jews and Christians, in which such information performs the humanistic attitudes of him who upholds human values and tolerance, respects diversity, and ensures the freedom of belief and religious worship. The Prophet Muḥammad never imposed anybody to become a Muslim at that time, he also allowed Christians doing their ritual activity inside the mosque. This paper also describes the context of the Prophet Muḥammad order to burn a mosque in Madīna. This paperr ejects some views of the orientalists, like Robert Spencer who wrote a book entitled The Truth about Muḥammad: The Founder of the Most Intolerant Religion in the World. This paper is the result of sīra Nabawīya’s study,whose data are derived from some canonical Ḥadīth and other historical resources.DOI: 10.15408/ref.v13i3.905